Pengaruh Budaya Organisasi Dan Gaya Kepemimpinan Terhadap Kinerja Auditor Dengan Struktur Audit Sebagai Variabel Moderasi - Sonny Marcel Kusuma, Gumulya; Kusumawaty, Mia (Jurnal Keuangan dan Bisnis, 2023)
The research intends to analyze the influence of organizational culture and leadership style on auditor performance. It used moderating variables, namely the audit structures. The sample was determined using convenience sampling. The number of auditor respondents was 46 people from the Public Accounting Firm in Palembang. Researchers used PLS-SEM data analysis. The result indicates that there is a positive influence of culture and leadership style on auditor performance. It also shows that the audit structure has not been able to moderate the influence of organizational culture and leadership style on performance.